Sleep Quality in Medical Staffs During the Outbreak of Coronavirus Disease 2019 in China: A Web-Based Cross-Sectional Study - Jiang, Furong; Xiao, Yi; Dong, Huixi; Liu, Siyu; Guo, Feng; Gong, Zhicheng; Xiao, Shuiyuan; Shen, Minxue; Zhou, Qiuhong; Li, Jianling (Frontiers in Psychiatry, 2021)
Background: To describe the sleep quality and its influencing factors among medical workers in different working status and staff types during the epidemic period of COVID-19. Methods: Through an online questionnaire survey, all medical staffs in Xiangya Hospital were invited to complete the general information, self-rating Scale of Sleep (SRSS), Depression, Anxiety and Stress Scale (dass-21), Social Support Rating Scale (SSRS), Simplified Coping Style Questionnaire (CSQ). Results: A total of 4,245 respondents completed the survey. Among them, 38.7% had sleep disturbance. After matching, the SRSS scores in the staffs who were assigned to the ICU of Union Hospital in Wuhan and working in the epidemic area of Xiangya hospital were no significant difference (P>0.05); the SRSS scores in the battlefront staffs was significantly higher than (P<0.05) those who were not treating the patients infected with COVID-19. The SRSS scores of nurses was significantly higher than that of doctors and hospital administrators (P<0.01). Anxiety, depression, and coping style were associated to sleep disturbance. Conclusion: Sleep quality of medical staffs is impaired during the epidemic period, especially among nurses, doctors and administrators who are working on the front line. Medical institutions should strengthen psychological services and coping strategies for medical staffs.